Barycentrická racionální interpolace. - Venclovský, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Tato bakálářská práce se zabývá odvozením barycentrického tvaru polynomiální interpolace a následně pak barycentrického tvaru racionální interpolace. Dále ukazuje nevýhody klasické racionální interpolace a zabývá se eliminací těchto nevýhod v jejím barycentrickém tvaru. Také ukazuje některé konkrétní metody řešení barycentrické racionální interpolace.

This bachelor thesis deals with deducing of barycentric form of polynomial interpolation and then barycentric form of rational interpolation. It shows disadvantages of classic rational interpolation and deals with elimination of these disadvantages in its barycentric form. It also shows some specific methods of barycentric rational interpolation.
Barycentric rational interpolation.
Keywords: barycentrická racionální interpolace; barycentrická Lagrangeova interpolace; racionální interpolace; barycentric rational interpolation; barycentric Lagrange interpolation; rational interpolation